Raising the Race : Black Career Women Redefine Marriage, Motherhood, and Community - Barnes, Riche J. Daniel, 1973- (Book collections on Project MUSE., 2016)
"Popular discussions of professional women often dwell on the conflicts faced by the woman who attempts to "have it all," raising children while climbing up the corporate ladder. Yet for all the articles and books written on this subject, there has been little work that focuses on the experience of African American professional women or asks how their perspectives on work-family balance might be unique. Raising the Race is the first scholarly book to examine how black, married career women juggle their relationships with their extended and nuclear families, the expectations of the black community, and their desires to raise healthy, independent children. Drawing from extensive interviews with twenty-three Atlanta-based professional women who left or modified careers as attorneys, physicians, executives, and administrators, anthropologist Riche J. Daniel Barnes found that their decisions were deeply rooted in an awareness of black women's historical struggles. Departing from the possessive individualistic discourse of "having it all," the women profiled here think beyond their own situation--considering ways their decisions might help the entire black community. Giving a voice to women whose perspectives have been underrepresented in debates about work-family balance, Barnes's profiles enable us to perceive these women as fully fledged individuals, each with her own concerns and priorities. Yet Barnes is also able to locate many common themes from these black women's experiences, and uses them to propose policy initiatives that would improve the work and family lives of all Americans."--Publisher's website.